Respuesta :
To solve this polynomial equation, we will need to factor the left side.
On the left, we have a a trinomial in a special form that
can be factored as the product of two binomials.
The trinomial on the left can be factored which makes life easier.
This factors as (x + 11)(x - 2) = 0.
This means that either x + 11 = 0 or x - 2 = 0.
Solving each equation from here, we get x = -11 or x = 2.
So the solution is {-11, 2}.
Answer:
2 and -11
Step-by-step explanation:
Step 1: Use the quadratic formula to solve for x
[tex]x=\frac{-b+-\sqrt{b^{2-4ac} } }{2a} \\x=\frac{-9+-\sqrt{9^{2}-4(1) (-22)} }{2(1)} \\x=\frac{-9+-\sqrt{169} }{2(1)}\\x=\frac{-9+-13 }{2}\\x1=\frac{-9+13 }{2}\\x1=\frac{4}{2} \\x1 = 2\\x2 = \frac{-9-13 }{2}\\x2 = \frac{-22 }{2}\\x2 = -11\\[/tex]
Therefore the values of 'x' that make the equation true is 2 and -11